2007
DOI: 10.1007/s11010-007-9644-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure of human renal carcinoma cells to PD98059 induces epithelial–mesenchymal transition-like phenotype and enhanced motility

Abstract: Extracellular signal-regulated kinases (ERK) have fundamental roles in tumor progression.However, human clinical trials have shown little or no effect of inhibitors of their upstream signaling molecule, mitogen-activated protein kinase/ERK kinase (MEK), in advanced cancers.To determine the molecular mechanism underlying the limited antitumor effect, we cultured two human renal carcinoma cell lines, ACHN cells and VMRC-RCW cells in the presence of a MEK inhibitor PD98059 for more than 4 weeks (PD98059-exposed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In this study, we demonstrated that stimulation with IL‐6 led to the activation of STAT3, AKT, ERK1/2 signaling pathways in AM‐EpiCs; however, only specifically blocking ERK1/2 or STAT3 signaling significantly abrogated IL‐6‐mediated EMT‐ and stem cell‐related gene expression in these cells. Of note, blocking ERK1/2 activity alone by PD98059 treatment induced the expression of certain EMT‐related markers in AM‐EpiCs, which was consistent with a previous study by Kanda et al, reporting that exposure to PD98059 increased cell motility by promoting EMT in human renal carcinoma cells . Since ERK and STAT3 were involved in a variety of tumor cell responses, inhibition of these signaling pathways was considered a potential strategy in the treatment of advanced cancer .…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we demonstrated that stimulation with IL‐6 led to the activation of STAT3, AKT, ERK1/2 signaling pathways in AM‐EpiCs; however, only specifically blocking ERK1/2 or STAT3 signaling significantly abrogated IL‐6‐mediated EMT‐ and stem cell‐related gene expression in these cells. Of note, blocking ERK1/2 activity alone by PD98059 treatment induced the expression of certain EMT‐related markers in AM‐EpiCs, which was consistent with a previous study by Kanda et al, reporting that exposure to PD98059 increased cell motility by promoting EMT in human renal carcinoma cells . Since ERK and STAT3 were involved in a variety of tumor cell responses, inhibition of these signaling pathways was considered a potential strategy in the treatment of advanced cancer .…”
Section: Discussionsupporting
confidence: 88%
“…ERK is activated by mitogen‐activated protein kinase ERK kinases (MEK 1 and 2), the only upstream molecules that can phosphorylate ERK. In vitro , PD98059, a MEK inhibitor, was found to decrease tumour cell proliferation by potentiating the cytotoxicity of chemotherapy in leukaemia, small cell lung cancer, cervical cancer, and colorectal cancer, while U0126, another MEK inhibitor, was shown to inhibit melanoma metastases 33–36. The reasons for the poor outcome of MEK inhibition in patients with advanced cancer are unknown 33.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , PD98059, a MEK inhibitor, was found to decrease tumour cell proliferation by potentiating the cytotoxicity of chemotherapy in leukaemia, small cell lung cancer, cervical cancer, and colorectal cancer, while U0126, another MEK inhibitor, was shown to inhibit melanoma metastases 33–36. The reasons for the poor outcome of MEK inhibition in patients with advanced cancer are unknown 33. In endometriosis, PD98059 decreases the in vitro production of pro‐inflammatory cytokines in endometriotic cells and decreases the in vitro viability of stromal eutopic endometrial cells 16, 25, 28.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, U0126 showed a slight effect on cell contraction. ERK1/2 effects could be mediated through tropomyosin phosphorylation in response to oxidative stress [27] or downregulating RhoA/Rho Kinase signalling [28]. Of note, changes in RhoA activity early during reoxygenation have been previously observed in our H/R model [5] even though further experiments should be done to clarify this relationship.…”
Section: Discussionmentioning
confidence: 63%